Analysis of Student Activity in the Learning Process Using the Communicative Language Teaching (CLT) Method - Ariani Ariani; Promadi Karim (PT. Anagata Sembagi Education, 2024)
Effective learning places students at the center of the learning process, where student activeness is key in creating an interactive and collaborative classroom atmosphere. Students' active participation through asking questions, expressing opinions, and cooperating with peers are important indicators of successful learning. However, in Arabic language learning, students often only master language structures without good communication skills. Traditional methods that emphasize memorization are less effective in building communicative language skills. This study aims to analyze the effectiveness of the Communicative Language Teaching (CLT) method in increasing student activeness at the Imam Ibnu Katsir Islamic Boarding School, Rumbai. This research used a mini-experiment method with three meetings on santriwati madrasah aliyah. The analysis was conducted using qualitative and quantitative approaches. The results showed that CLT was able to increase student activeness, especially in listening and speaking skills. The most active student activities include listening, participating in discussions, and making conversations with a participation rate of 85%. This study concludes that CLT is a very effective method to improve students' activeness and communication skills in Arabic language learning. However, this study has limitations on the number of trials, so further research with more comprehensive data is recommended.